Effect of high-moisture grain on availability of phosphorus for swine - Trotter, M.; Allee, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A feeding trial and two phosphorus balance studies were conducted to compare the availabilities of phosphorus from high-moisture sorghum grain treated with propionic acid (1.2% acid, 23% moisture), grain stored in an oxygen limiting structure (27% moisture), and field-dried sorghum grain (13% moisture). Bone and phosphorus retention data indicated that the phosphorus in high-moisture sorghum grain is more available than phosphorus in field-dried sorghum grain.
Keywords: Swine; High-moisture grain; Phosphorus